Raison d'Étre - Robinson, Mike (ARCTIC, 1998)
. Sometimes, amidst the rush and complexity of what passes for academic life in the last years of the second millennium, we miss the opportunity to reflect quietly on the reasons why we do what we do. This commentary is being written in the boardroom/poster room of the Arctic Institute's Kluane Lake Research Station in the Yukon. All around me on the walls are poster displays on such topics as the University of Ottawa Field School Program from 1975 to 1998, How Do Glaciers Surge?, Vertebrate Community Dynamics in the Yukon Boreal Forest, and the Mount Logan Ice Core Climatic Change Project. These displays focus on past and current projects at the research station, and are pinned up to explain to this season's field school students, graduate student researchers, and the occasional inquisitive tourist just what the Arctic Institute does in its 37th year of logistical support to Yukon science. . when I met with my colleagues on the Kluane Lake Research Station Users' Committee, we talked of our obligation to submit a Major Facilities Access Grant application to NSERC by October 1 to ensure that all of this tradition, science, and exuberant discovery can continue. Amidst a general air of good-humoured collaboration, social, biological, and physical scientists reviewed their progress over the past year and talked of their research dreams for the future. While the works conveyed strong commitment and rigor in the cause, the faces shone with the excitement of another good field season, renewed Yukon friendships, and the joy of sharing learning in one of the most beautiful places on earth. . Behind the kitchen counter, . I spied my 16-year-old son Lance washing dishes as a summer volunteer. . Yesterday he told me that Andy Williams, the base manager, had taken him up in his Helio-Courier airplane to see the Icefield Ranges from 10,000 feet, and that it had been "one of the best things I've ever done in my life." . As we cruise down the Alaska Highway back to the land of e-mail, appointment books, and commercial ...